If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-2(3x+3)=1/3(6-2x)
We move all terms to the left:
-2(3x+3)-(1/3(6-2x))=0
Domain of the equation: 3(6-2x))!=0We add all the numbers together, and all the variables
x∈R
-2(3x+3)-(1/3(-2x+6))=0
We multiply parentheses
-6x-(1/3(-2x+6))-6=0
We multiply all the terms by the denominator
-6x*3(-2x+6))-(1-6*3(-2x+6))=0
Wy multiply elements
-18x^2(--18x(-=0
We use the square of the difference formula
-18x^2(+18x(-=0
| u3+ 8=12 | | 3(x-2)+2x=-19 | | 10n+8-12n-5=21 | | n+8n=30 | | 5a^2-21=8a | | f/3-20=-28 | | 7w-10=25 | | 2t^2+5t-14=0 | | 2.5(7-y)+1.6y=13 | | 24+7u=73 | | 28x+30=20x+26 | | 3(4x+2=20x-9x-2 | | g/2+13=26 | | -3n+2+7-5n=-23 | | 0.84=x-9.5 | | 2p-16+3p=4 | | 4(5w-7)=20w+2 | | p+4/15;p=4/5 | | -4n-3+6n-4=-21 | | 4(4x+3)=19x+9—3x+3 | | 15-y=28 | | -32=-8k+7k | | 62+55+x=180 | | 16=-4+2w | | 3^(x+6)=34. | | -0.9p=-2.7 | | 9m−4=68 | | –4w=–16 | | 8x=3x32 | | -7.7n-6.7=9.2 | | .35(x+4)=3(2x-6) | | 10r+21=91 |